IMPROVING NARRATIVE WRITING ACHIEVEMENT OF THE TENTH GRADERS OF SMA NEGERI UNGGUL 4 PALEMBANG - Muhammad Irwansyah Putra; Erlina Erlina; Lingga Agustina Suganda (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2019)
The objectives of this study were to find out whether or not (1) there was any significant difference in narrative writing achievement between before and after the tenth graders of SMA Negeri Unggul 4 Palembang were taught by using POW+WWW W=2 H=2 strategy and (2) there was any significant difference in narrative writing achievement between the students who were taught by using POW+WWW W=2 H=2 strategy and the those who were not. The sample of this study was tenth graders of SMA Unggul Negeri 4 Palembang chosen by using convenience sampling method. There were two groups, namely experimental group and control group. To collect the data, pre-test and post-test were given. The data were analyzed using paired sample t-test and independent sample t-test in SPSS version 22. The results of paired sample t-test showed that there was a significant difference in narrative writing achievement between before and after the tenth graders of SMA Negeri Unggul 4 Palembang were taught by using POW+WWW W=2 H=2 strategy as the r-value was lower than 0.05 (0.000 < 0.05). The results of independent sample t-test showed that there was a significant difference in narrative writing achievement between the students who were taught by using POW+WWW W=2 H=2 strategy and those who were not as the r-value was lower than 0.05 (0.000 < 0.05). In conclusion, using POW+WWW W=2 H=2 Strategy is effective to improve narrative writing achievement of the tenth graders of SMA Unggul Negeri 4 Palembang.